LB006 Microvascular cerebral blood flow response to intrathecal nicardipine is associated with delayed cerebral ischemia in subarachnoid hemorrhage. (26th July 2022) - Sathialingam, E; Cowdrick, K; Liew, A; Akbik, F; Samuels, O; Kandiah, P; Sadan, O; Buckley, E
Abstract : Introduction: One common complication of subarachnoid hemorrhage (SAH) is cerebral vasospasm, a maladaptive response that can lead to a secondary stroke. Intrathecal (IT) administration of nicardipine holds promise as a safe treatment for cerebral vasospasm, when given every 6-8 hours for ~2 weeks upon confirmed diagnosis of cerebral vasospasm. Preliminary data suggest that IT nicardipine induces macro vascular vasodilation and reduces the risk of secondary stroke. 1 However, no work has been done to assess the micro vascular effects of IT nicardipine. Herein, we utilize diffuse correlation spectroscopy (DCS) to characterize the microvascular cerebral blood flow (CBF) response to IT nicardipine in a cohort of medium-high grade non-traumatic SAH patients. We hypothesize that (1) the first dose of IT nicardipine will increase microvascular CBF from pre-administration levels and that these changes will be detectable by DCS and (2) the CBF response to IT nicardipine will reach a steady state by day 3 of treatment. Methods: Twenty medium-high grade non-traumatic SAH patients were enrolled. Longitudinal DCS monitoring was performed before, during, and for up to 2h after IT nicardipine administration on days 1, 2, and 3 by securing a DCS sensor 2 on the forehead of the hemisphere with the vasospasm. To calculate a relative change in CBF (rCBF(t)), the DCS blood flow index (BFI) time series was normalized to the mean BFI in the 5 minutes immediately prior to nicardipine. BFI was compared to TCD mean velocities taken on the same day. Results: DCS BFI was significantly correlated with mean TCD velocities ( rs =0.68, p=0.001, figure 1a ). CBF increased significantly after IT nicardipine administration on days 1 and 2 (p<0.001, figure 1b ). By the third day, CBF was reduced, suggesting that nicardipine had reached a steady state concentration in the brain. Given the heterogeneous CBF response to the first dose, we used a latent class mixture model to identify two distinct classes of CBF response; patients in Class 1 (n=13, figure 1c ) exhibited a steady rCBF increase, whereas patients in Class 2 (n=5, figure 1c ) showed minimal rCBF change. The DCI frequency at 1 month was significantly different between classes (p<0.001). Discussion: Our results suggest that IT nicardipine achieves the desired effect of microvascular vasodilation in the majority of patients after the first dose of treatment, while those patients who did not respond developed a secondary stroke. DCS may be a powerful tool to monitor the therapeutic efficacy of nicardipine treatment and to better guide clinical decisions for reducing secondary stroke incidence. References: doi:10.3171/2020.12.jns203673 doi:10.1117/1.nph.6.3.035006 Disclosures: E. Sathialingam: None. K. Cowdrick: None. A. Liew: None. F. Akbik: None. O. Samuels: None. P. Kandiah: None. O. Sadan: None. E. Buckley: None.